Exploring first-time pregnant women's motivations for planning vaginal delivery: A qualitative study - Fatemeh Darsareh; Teamur Aghamolaei; Minoo Rajaei; Abdoulhossain Madani (Wolters Kluwer Medknow Publications, 2018)
Background: In spite of medical indications, preferences for the mode of delivery are influenced by several factors. However, as the literature suggests, the underlying motivation of women choosing vaginal delivery is rarely attended to. The current study aimed to explore first-time pregnant women's motivation for planning vaginal delivery. Materials and Methods: An exploratory design with in-depth interviews was employed from September 2015 to March 2016. Participants were asked key questions about their beliefs about vaginal delivery, perceived outcomes of vaginal delivery, the impact of others perspectives on their decision, and factors that might inhibit or facilitate vaginal delivery. A community advertisement was placed in obstetricians' offices, public health departments, as well as beauty salons throughout the city of Bandar Abbas, Iran, to enroll target participants. All interviews were tape-recorded, transcribed, and subsequently analyzed. Results: Twelve pregnant women within the age range of 19-33 years volunteered to participate. Ninety four initial codes were obtained. These codes were then summed up into three themes as well as six subthemes. The three themes specified were personal beliefs, deliberation and risk assessment, and personal autonomy. Conclusions: A number of key motivating factors such as fast recovery after vaginal delivery, immediate breastfeeding, and powerful bonding were identified, which were influential in choosing vaginal delivery. Awareness of the fact that the provided information shapes women's beliefs and can lead to attitude changes, midwives played a key role in shaping positive and healthy attitudes toward natural birth giving as well as empower them to make autonomous decision.